2020
DOI: 10.1101/2020.11.22.393538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial respiration contributes to the interferon gamma response in antigen presenting cells

Abstract: The immunological synapse allows antigen presenting cells (APC) to convey a wide array of functionally distinct signals to T cells, which ultimately shape the immune response. The relative effect of stimulatory and inhibitory signals is influenced by the activation state of the APC, which is determined by an interplay between signal transduction and metabolic pathways. While toll-like receptor ligation relies on glycolytic metabolism for the proper expression of inflammatory mediators, little is known about th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Remarkably, PD-L1 inducible expression has been reported to be upregulated through IFN-γ activation of the NF-κB pathway [ 42 ]. Interestingly, a recent work identified that the ETCI function is essential for IFN-γ signaling because upon the genetic or pharmacological function abrogation of exclusively the first ETC complex, IFN-γ signaling is impaired and PD-L1 levels are decreased [ 45 ]. This study suggests that the NAD+ driven by the functional ETCI is essential for IFN-γ signaling as the impaired activity of exclusively ETCI is enough to decrease the IFN- γ signaling pathway and PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, PD-L1 inducible expression has been reported to be upregulated through IFN-γ activation of the NF-κB pathway [ 42 ]. Interestingly, a recent work identified that the ETCI function is essential for IFN-γ signaling because upon the genetic or pharmacological function abrogation of exclusively the first ETC complex, IFN-γ signaling is impaired and PD-L1 levels are decreased [ 45 ]. This study suggests that the NAD+ driven by the functional ETCI is essential for IFN-γ signaling as the impaired activity of exclusively ETCI is enough to decrease the IFN- γ signaling pathway and PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…OxPhos is most directly regulated by the activity and the amount of complexes I through V that carry it out (Hüttemann et al , 2007). Upregulation of OxPhos is known to be required for many important immune cell functions, such as B cell antibody production (Price et al , 2018), pathogenic T‐cell differentiation during autoimmunity (Shin et al , 2020), CD8 + memory T‐cell development and expansion (van der Windt et al , 2012), T‐reg suppressive function (Weinberg et al , 2019), T cell activation by macrophages (Kiritsy et al , 2021), and the maturation of anti‐inflammatory macrophages (Vats et al , 2006). However, what changes immune cells initiate to upregulate OxPhos remains unclear and how such shifts in metabolism could influence immune cell migration is unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest a compelling role for mitochondria in antigen processing and presentation 79,80 as well as in cancer immune evasion 81 . Important considerations include strategies to counteract the inactivation of the major histocompatibility class 1 pathway, and how MTD‐induced inhibition of respiration affects cytokine (e.g., interferon gamma) response in antigen‐presenting cells 82,83 …”
Section: Unanswered Questionsmentioning
confidence: 99%
“…81 Important considerations include strategies to counteract the inactivation of the major histocompatibility class 1 pathway, and how MTD-induced inhibition of respiration affects cytokine (e.g., interferon gamma) response in antigen-presenting cells. 82,83 How epigenetic modifications (DNA methylations, histone modifications, mRNA expression modulation) that affect changes in the gene expression (not caused by changes in the DNA sequences) are influenced by MTDmediated repression of mitochondrial respiration in cancer cells is not known. Epigenetic modifications have been used as predictive biomarkers in cancer.…”
Section: Unanswered Questionsmentioning
confidence: 99%